Towards a public architectural history: Collective-use facilities and community engagement in Portugal and Spain - Agarez, R. C.; Pascoal, A. M.; Herrera-Pineda, I. (International Public History, 2025)
The sustained use and reuse of existing buildings is key in addressing social inequality and reinforcing sustainability and resilience in peripheral, disadvantaged communities of the so-called developed world. Collective-use facilities built since the 1940s, the outcome of individual and common efforts, carry decades of service to communities and are repositories of both material and experiential values. Knowing their history of production and use is essential in reassessing their relevance for current and future needs: to be effective, this knowledge must be appropriable and relatable, co-created, and widely shared. This article discusses how such premises are put to the test in Arquitectura Aqui, a research and dissemination initiative underway in communities in Portugal and Spain. Using different cases in both countries to examine specific goals and methodologies, challenges and results, we suggest that local engagement in co-researching and co-narrating the past and present of buildings and their role in collective life, in a participation and dissemination platform, might contribute to putting into practice a public architectural history of community buildings.